Factors Influencing Vertical Transmission of Psittacine Bornavirus in Cockatiels (Nymphicus hollandicus) - Link, Jessica; Herzog, Sibylle; Gartner, Anna Maria; Bücking, Bianca; König, Matthias; Lierz, Michael; Justus Liebig University Giessen (My University, 2022)
The transmission of parrot bornavirus is still not fully understood. Although horizontal transmission through wounds can be one route, vertical transmission is still discussed. PaBV RNA and PaBV antigen were detected in psittacine embryos, but isolation of the virus failed, raising doubts about this route. In this study, cockatiels were infected either as adults (adult group) or during the first 6 days after hatching (juvenile group) and raised until sexual maturity to breed and lay eggs. A total of 92 eggs (adult group: 49, juvenile group: 43) were laid and incubated until day 17. The embryos and yolk samples were examined by RT-PCR for PaBV RNA and by infectivity assay for infectious virus. In the adult group, 14/31 embryos (45.2%) and 20/39 (51%) of the yolk samples demonstrated PaBV RNA in the PCR. Isolation of PaBV was not possible in any embryo of this group, but it was achieved in six yolk samples from one female. Anti-PaBV antibodies were detected in the yolk samples after seroconversion of all female parents. In the juvenile group, 22/29 embryos (74.9%) were positive for PaBV RNA. In 9/21 embryos (42.9%), PaBV isolation was possible. PaBV RNA was detected in 100% and infectious virus in 41% of the yolk samples. Anti-PaBV antibodies were detected in all yolk samples. For the first time, successful vertical transmission of PaBV was proven, but it seems to depend on the age when the parent birds are infected. Therefore, the age of the bird at time of infection may be an important factor in the occurrence of vertical transmission.
Keywords: avian bornavirus; Bornaviridae; psittaciform 1 orthobornavirus; proventricular dilatation disease; neurological disease; virus transmission; age dependency; immunopathogenesis; species conservation; vertical transmission; ddc:630